2022
DOI: 10.1037/pspp0000435
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in contingencies between situation characteristics and personality states.

Abstract: Contingencies between situational variables and psychological states have been proposed as key individual difference variables by many theoretical approaches to personality. Despite their relevance, the basic properties, nomological correlates, and factor structure of individual differences in contingencies have not been examined so far. We address these fundamental questions in five studies with overall N = 952 participants and N = 32,052 unique assessments. Individual differences in situation characteristic-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
3

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(40 citation statements)
references
References 119 publications
8
22
3
Order By: Relevance
“…More broadly, our findings are in line with theories that emphasize individual differences in situational contingencies as important aspects of personality (e.g., Denissen & Penke, 2008; Mischel & Shoda, 1995). Whereas much of the prior literature on contingencies found no significant associations with personality traits (Kuper et al, 2022; Sherman et al, 2015), we observed the expected associations between trait narcissism and emotional reactivities. One crucial difference is that we preregistered and examined contingencies derived from theoretical models, such as process models of narcissistic status pursuit (Grapsas et al, 2020) and three-factor models of narcissism (e.g., Krizan & Herlache, 2018; Miller et al, 2017; Wright & Edershile, 2018).…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…More broadly, our findings are in line with theories that emphasize individual differences in situational contingencies as important aspects of personality (e.g., Denissen & Penke, 2008; Mischel & Shoda, 1995). Whereas much of the prior literature on contingencies found no significant associations with personality traits (Kuper et al, 2022; Sherman et al, 2015), we observed the expected associations between trait narcissism and emotional reactivities. One crucial difference is that we preregistered and examined contingencies derived from theoretical models, such as process models of narcissistic status pursuit (Grapsas et al, 2020) and three-factor models of narcissism (e.g., Krizan & Herlache, 2018; Miller et al, 2017; Wright & Edershile, 2018).…”
Section: Discussioncontrasting
confidence: 99%
“…In addition, we showed that the individual differences in status contingencies were somewhat stable over time. The short-term stability correlations within waves (Study 1: .43/.39, Study 2: .49/.45) were comparable to those found in previous research (Kuper et al, 2022). Importantly, the stabilities were relatively large across longer timeframes (i.e., .57 [Study 1] and .51 [Study 2] for a time lag of 2 months between waves), supporting the conceptualization of contingencies as stable individual difference variables.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations